European cross-border banking and banking supervision - Singh, Dalvinder, 1970- (Oxford : Oxford University Press, 2020)
This book provides timely analysis of the cross-border exercise of banking activity in the EU and its supervision, from the perspective of the 'home-host rule'. It examines the current system and the efficacy of recent reforms considering whether the centralization of decision making and a more effective mutualization of financing tools could increase the efficiency of the EU banking system. The EU banking market is very integrated since banking institutions based in the Union are free to perform their activities within the common market. This has allowed EU banking institutions to significantly increase their cross-border operations. This way of working is based on the home country control principle according to which EU institutions performing cross-border activities continue to be supervised by their home country supervisor. However, this system has raised challenges for effectively performing supervision and resolution.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 29, 2020).
Keywords: Banks and banking -- European Union countries